Effect of Factors of Body Composition, Body Stature and Distribution of Lifters in the Weight Categories - Adamfi, Attila; Szabo, Andras S (Journal of Sports Research, 2020)
It was demonstrated that for the biomechanical evaluation of the relative performance the complex system (body + barbell) should be taken into account. Another factor is the body-composition (muscle-, fat- and bone ratios) of the lifters. The most dominant is the muscle-ratio, which is significantly less in the super-heavyweight category than in the others. Modification parameter is the physique of the athlete (dominantly the body height), because to reach higher level with the barbell during the pull it is necessary to have higher speed, so consequently the lifter has to perform higher acceleration and needs more strength to carry it out. The body height is important from point of view of energetics, as well – the physical work performed by a taller lifter is more – influencing also the regeneration time and the loadability, reducing the level of sport result. The physique and body composition has an impact also on the movement-structure and the technical skill (level) of attempts. In the super-heavyweight the technique is often far from the optimum, concerning the biomechanical requirements (e.g. the disturbing effect of the big belly). The last factor is the distribution of lifters in the different categories, surely if the number of lifters is not similar in the different categories, the expectable sport level can be also different.